Implementation Of Management Information Systems And Internet Of Things In Improving The Economy And Developing Human Resources To Expand Export Market Penetration Of Tenun Ikat Troso Jepara - Baharuddin, Hamsinah; Rusilowati, Umi; Taryo, Taswanda (Magister Manajemen, Universitas Pasundan, 2024)
Research for the International Community Service (PKM-I) was carried out to formulate strategies and programs for the development of Jepara's Troso Naviza Ikat Woven Small and Medium Enterprises (MSMEs). Strategies need to be implemented to develop MSMEs, including by increasing the capabilities of related human resources. There is then a need to create various innovative products and carry out digital promotional strategies, so that MSME products can go global. The Magister Management Study Program (MM Program) together with the Syah Alam Polytechnic (PSA) Selangor Malaysia on 24-27 September 2024 conducted PKM-I with these MSMEs. The initial study stated that these MSMEs had problems regarding the lack of quantity of sales of ikat weaving exports abroad. Apart from that, these MSMEs need to improve their human resources capabilities to increase their ability to export products abroad and there is still a lack of understanding of digital promotion using IoT (Internet of Things) and MIS (Management Information System). In addition, human resource development is needed to expand product export penetration abroad. During PKM-I, a directing method was carried out using IoT and MIS for digital product promotion and human resource development as well as evaluating the results of PKM-I that had been implemented. It is hoped that all Troso Jepara Ikat Weaving MSME business players will master the strategic matters of exporting ikat weaving abroad based on MIS and IoT. This is also specifically related to digital marketing as well as human resource development. Indeed, these MSMEs will be able to expand product export penetration abroad in the near future.